Effect of simultaneous surgical treatment of severe coronary artery disease and lung cancer. Issue 2 (February 2019) - Li, Zhi; Liu, Ban; Ge, Wen; Zhang, Wei; Gu, Chang; Liu, Jingjing; Ke, Xianting; Zhang, Yangyang
Objective: The co-incidence of lung cancer and coronary artery disease (CAD) is increasing in patients of advanced age. This study was performed to demonstrate the efficiency and safety of simultaneous coronary artery bypass grafting and lung cancer surgery in a selected group of older patients. Methods: Twenty patients with severe CAD and coexisting lung cancer underwent simultaneous surgical interventions (Group A), and 20 patients with lung cancer underwent an isolated lung cancer operation (Group B). In Group A, the combined operations were carried out through 2 incisions in 3 patients, a single incision in 14 patients, and median sternotomy for heart surgery and thoracoscopic lobectomy for lung cancer in 3 patients. The single-incision approach was used in all patients in Group B. Results: The operation time was longer and the blood loss volume was larger in Group A than B. No significant between-group differences were found in the 5-year relapse-free survival rate or 5-year survival rate. Conclusions: The simultaneous performance of lung cancer surgery and cardiac surgery was effective and evidently safe in Group A. This treatment approach enabled earlier lung cancer resection and avoidance of the eventual complications associated with further surgical procedures.